1996
DOI: 10.2105/ajph.86.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth retardation and premature delivery: the influence of maternal smoking and psychosocial factors.

Abstract: OBJECTIVES. This study investigated the influence of psychosocial stress, maternal schooling, social support, psychological well-being, alcohol, and smoking on intrauterine growth retardation and premature delivery. METHODS. At a Copenhagen university hospital, 2432 pregnant women completed a questionnaire on general health, psychosocial stressors, and sociodemographic characteristics. RESULTS. In 212 cases (8.7%) the women delivered prematurely. Preterm delivery as associated with psychosocial stress (adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
133
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(146 citation statements)
references
References 43 publications
8
133
2
3
Order By: Relevance
“…The negative impact of smoking on pregnancy outcome has been known for decades [13,23]. In addition to other results [6], the presented study showed that it is not CSA itself but physical abuse, likely in combination with CSA, which seems to be relevant for this association.…”
Section: Discussionsupporting
confidence: 63%
“…The negative impact of smoking on pregnancy outcome has been known for decades [13,23]. In addition to other results [6], the presented study showed that it is not CSA itself but physical abuse, likely in combination with CSA, which seems to be relevant for this association.…”
Section: Discussionsupporting
confidence: 63%
“…A third reason is that only few studies have controlled the association for confounding variables such as parity, gestational age (GA), socio-economic status, age, morbidity and anthropometry of the mother. The findings in most studies, however, suggest that the contribution of maternal stress to LBW, either directly or mediated through health-risk behaviours, such as cigarette smoking, alcohol intake (Pagel et al, 1990;Pritchard & Teo, 1994;Copper et al, 1996;Nordentoft et al, 1996;Jacobsen et al, 1997;Paarlberg et al, 1999), and probably coffee intake, should be considered seriously (Aarst & Vingerhoets, 1993;Hedegaard et al, 1996). Therefore, we decided to carry out a large prospective study, evaluating: (1) the associations between maternal psychological stress, distress and LBW, prematurity, and IUGR; (2) the interactions between maternal stress, distress and smoking, alcohol and coffee intake; (3) the prevalences of stress and distress in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking or drinking alcohol (at least 'occasionally') were considered disadvantageous for the child since these conditions are considered harmful by many authors as they can cause intrauterine growth retardation and other adverse health outcomes like behavioural and psychosocial problems in childhood (18)(19).…”
Section: Introductionmentioning
confidence: 99%